Implementation of User Acceptance Tests in Capstone Project Information Systems - Wiradarma, Made; Pradana Adnyana, Putu Gede; ER, Ngurah Indra; Purnama, Fajar; Saputra Iskandar, Adi Panca; Sukadarmika, Gede (Journal of Electrical, Electronics and Informatics; Vol 8 No 2 (2024): JEEI (December 2024), 2025)
The Capstone Project Information System (SICP) was developed to manage the administration of capstone projects in the Electrical Engineering Study Program at Udayana University, aiming to minimize repetitive tasks and reduce the potential for human error. Testing was conducted using the User Acceptance Testing (UAT) method to ensure the system meets the needs and expectations of end users. UAT involved various user roles and utilized the Likert scale for evaluation. The test results indicate that the system operates according to functional specifications, and users are satisfied with the interface and functionality. The overall UAT score of 0.939 shows that SICP has successfully met user needs very well. This testing ensures that SICP is ready for use and contributes to the accreditation achievement from the Indonesia Accreditation Board for Engineering Education (IABEE).